"The Balloon Plug Concept" for Tricuspid Valve Repair. Issue 1 (January 2015) - Bajona, Pietro; Salizzoni, Stefano; Vandenberghe, Stijn; Bruce, Charles J.; Speziali, Giovanni; Zehr, Kenton J.
<x xml:space="preserve">Abstract</x> Objective Functional tricuspid regurgitation (TR) is recognized as a significant cause of morbidity and mortality in cardiothoracic surgery. We hypothesized that a variably expandable, transvalvular balloon mounted on a catheter could be percutaneously inserted and fixed to the right ventricle apex. This novel approach could provide a minimally invasive way to eliminate clinically relevant TR caused by annular dilatation. This study was performed to test the ex vivo hemodynamic effects and the feasibility of the "balloon plug concept." Methods Twenty harvested calf tricuspid valves were placed in a mechanical simulator. Tricuspid regurgitation was created by annular stretching and displacement of the papillary muscles so as to create central TR. A flexible catheter with a 4-cm–long, soft, fusiform balloon was positioned across the valve so that the balloon was suspended centrally across the valve annular plane. After activating the mechanical ventricle, data were collected with balloon inflation volumes of saline from 5 to 20 mL. Transvalvular pressure gradients and leaflet mechanics were evaluated with incremental inflation. Results In all cases, 5-mL inflation did not significantly reduce TR and 20-mL inflation caused obstruction to antegrade flow (mean transvalvular gradient > 4 mm Hg). Inflation between 10 and 15 mL caused significant reduction in TR with acceptable transvalvular gradients (<3 mm Hg). Conclusions The balloon plug concept showed promising ex vivo hemodynamic results. In vivo investigations are warranted to evaluate percutaneous techniques, thrombogenicity, and effects of repeated balloon-leaflet contact on valve integrity.